5m(-3m+2m)=

Simple and best practice solution for 5m(-3m+2m)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5m(-3m+2m)= equation:


Simplifying
5m(-3m + 2m) = 0

Combine like terms: -3m + 2m = -1m
5m(-1m) = 0

Remove parenthesis around (-1m)
5m * -1m = 0

Reorder the terms for easier multiplication:
5 * -1m * m = 0

Multiply 5 * -1
-5m * m = 0

Multiply m * m
-5m2 = 0

Solving
-5m2 = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Divide each side by '-5'.
m2 = 0

Simplifying
m2 = 0

Take the square root of each side:
m = {0}

See similar equations:

| 39n+1017=39+1017 | | r=5.66 | | 6m-3=1 | | (-3)*5+(-3)*x= | | 6n-4n=n+18 | | 16+7x-5+x=11x-3-2x | | 10(t-2)+8t=6(3t+3)-10 | | 9-3x-7-11x=4 | | R*7+1=50 | | 2x^3-20x^2+48x=0 | | 3x^3-12x^2-36x=0 | | (x^4-8x^3+18x^2-15)=0 | | 5x+6=-x^2 | | -9(4x+7)+1= | | 16a^3+32a^2+12a=0 | | 3c-(-7c)= | | 3x+7y=32 | | 42a-36= | | 2x^2+5x-11=0 | | -(4y+2)-(-3y-8)=3 | | 3c-(-7c)+10= | | f/45=-3 | | 3c-(-7)+10= | | 5x+3y=32 | | (p^2-2)=0 | | 42a-6= | | -7w=7 | | 2=6x-3-x | | 5(x+2)=6(x-5) | | 2x+2=3x+6 | | 5x^3+2x^2-45x-18=0 | | 5x+2=6x-5 |

Equations solver categories